ANALISIS KEPUASAN PELANGGAN PADA PELAYANAN AIR BERSIH DI PDAM TIRTA BENING KABUPATEN PATI - Arin Nurwidya; Hery Sawiji; Tri Murwaningsih (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2022)
The purpose of this study is to determine: (1) Customer satisfaction with clean water services (2) Obstacles faced in the implementation of clean water services, (3) Efforts performed by PDAM Tirta Bening, Pati Regency in solving obstacles of clean water services.This type of research is descriptive qualitative with a case study approach. Sources of data in this study came from informants, events, and documents. The sampling technique used was purposive and snowball sampling. Data collection techniques were done through interviews, observation, and documentation. The results of this study indicate that: (1) Customer satisfaction on water services related to tangible; assurance; responsiveness; and empathy dimensions are great. Nevertheless, the customer satisfaction related to reliability dimension is low and it needs some improvements, (2) Constraints faced in the implementation of clean water services are: (a) Lack of water sources, (b) Old piping networks, (c) Power outage by PLN, and (3) Efforts made in facing obstacles related to clean water services are: (a) Finding and opening sources of raw water, (b) Changing pipes gradually, (c) Increasing the number of generators.